2019
DOI: 10.3354/meps12933
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and intra-population patterns in polar bear foraging ecology in western Hudson Bay

Abstract: Climate-mediated sea ice declines have led to alterations in ecosystem composition, phenology, and primary productivity, potentially altering trophic dynamics in Arctic marine ecosystems. As one of the Arctic's top predators and a species dependent on sea ice habitat for survival, polar bears Ursus maritimus are at risk of habitat loss from sea ice declines, and therefore have been used to monitor the effects of climate change in the Arctic. We used stable isotope (δ 15 N, δ 13 C) values of 806 hair samples co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 57 publications
(140 reference statements)
2
17
0
Order By: Relevance
“…Sea ice is the most important single factor influencing polar bear demographic responses in the changing Arctic marine ecosystem ( Stirling et al , 1999 ; Bromaghin et al , 2015 ; Lunn et al , 2016 ). Our results are consistent with the association between earlier breakup/later freeze-up and declining body condition ( Stirling et al , 1999 ; Obbard et al , 2016 ; Sciullo et al , 2016 ; Laidre et al , 2020 ), increased stress ( Boonstra et al , 2020 ), altered foraging ecology ( McKinney et al , 2009 ; Johnson et al , 2019 ), and reduced reproduction/survival rates and abundance ( Regehr et al , 2007 ; Rode et al , 2010 ; Lunn et al , 2016 ; Obbard et al , 2018 ) reported in various polar bear populations including WH, Southern Beaufort Sea, Southern Hudson Bay and Baffin Bay. Changes to energetic intake and expenditure in response to sea ice dynamics have consequences for energetic balances ( Pagano et al , 2018 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Sea ice is the most important single factor influencing polar bear demographic responses in the changing Arctic marine ecosystem ( Stirling et al , 1999 ; Bromaghin et al , 2015 ; Lunn et al , 2016 ). Our results are consistent with the association between earlier breakup/later freeze-up and declining body condition ( Stirling et al , 1999 ; Obbard et al , 2016 ; Sciullo et al , 2016 ; Laidre et al , 2020 ), increased stress ( Boonstra et al , 2020 ), altered foraging ecology ( McKinney et al , 2009 ; Johnson et al , 2019 ), and reduced reproduction/survival rates and abundance ( Regehr et al , 2007 ; Rode et al , 2010 ; Lunn et al , 2016 ; Obbard et al , 2018 ) reported in various polar bear populations including WH, Southern Beaufort Sea, Southern Hudson Bay and Baffin Bay. Changes to energetic intake and expenditure in response to sea ice dynamics have consequences for energetic balances ( Pagano et al , 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…Adult females and juveniles are often vulnerable demographic groups and their condition can influence population trends by affecting reproduction and survival rates ( Lockyer, 1986 ; Miller et al , 2011 ; Fortune et al , 2013 ; Keay et al , 2018 ). The small body size, dietary constraints, energetic demands of growth, risk of kleptoparasitism from larger bears and inexperienced hunting skills of younger bears make them more vulnerable to reductions in sea ice and thus prey availability ( Stirling, 1974 ; Rode et al , 2010 ; Thiemann et al , 2011a ; Pilfold et al , 2016 ; Johnson et al , 2019 ; Laidre et al , 2020 ). In contrast, adult males can best buffer against sub-optimal conditions given their larger body size, broader diets, more effective hunting skills and kleptoparasitism from smaller bears ( Stirling, 1974 ; Regehr et al , 2007 ; Thiemann et al , 2011a ; Pilfold et al , 2016 ; Johnson et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary estimates reconstructed using bulk isotopic values reflect a mixture of influencing factors and often provide results that are inconclusive or muddled (28). This is especially true in systems where the isotopic baseline supporting production changes or the trophic level that animals feed at have shifted (29,30). The δ 15 N values of resources supporting primary production can shift substantially, both spatially and temporally, depending on the balance of biogeochemical processes affecting available N sources (NO3 -, NO2 -NH4 + , N2) within an ecosystem (31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…10% for three consecutive days was used as the date of freeze-up (Etkin 1991;Stirling et al 1999;Lunn et al 2016). The length of the open water period (i.e., when bears are on land) was calculated as the date of freeze-up minus the date of breakup, then further subtracting 25 days due to the bears arriving onshore approximately 21 to 28 days after breakup (Stirling et al 1999;Castro de la Guardia et al 2017;Johnson et al 2019). In addition, the Arctic Oscillation winter index (AOw) and the North Atlantic Oscillation winter index (NAOw) were extracted for each year to examine broad climate variability.…”
Section: Environmental Datamentioning
confidence: 99%